Clinicopathological features, prognosis, and fertility outcomes in Chinese Han women treated for ovarian yolk sac tumor: A retrospective case series study from two tertiary-care academic medical centers. Issue 29 (22nd July 2022) - Qin, Li; Wang, Bo; Wang, Zaiping; He, Du
Abstract : Objective: Ovarian yolk sac tumor (YST) is a very rare malignant tumor in young women. This study aimed to explore the clinicopathological prognostic characteristics and reproductive outcomes of Chinese Han patients. Methods: To describe a case series study, we reviewed the clinicopathological data of 50 YST patients treated from 2 tertiary medical academic medical centers from January 2009 to December 2019. The Akaike information criterion was used to select variables. The influence of relevant characteristics on prognosis factors was analyzed by the Cox proportional hazard model. Results: The median follow-up time was 64.5 months (range from 3 to 124 months). The median age was 22.7 years (3 to 34 years). Abdominal pain (54.0%) or mass (42.0%) were the most common clinical symptoms in the early stage of diagnosis. The tumors were located bilaterally in 4 cases. 27 patients, 7 patients, 13 patients, and 3 patients were in stage I, II, III, and IV, respectively. Twenty-one stage I patients and 12 stage II to IV patients underwent fertility-preserving surgery. Of the 50 patients who received postoperative chemotherapy, 49 received the BEP regimen. At the last follow-up, 92% of the patients were still alive. The overall survival rate and disease-free survival rate were 91.6% and 90.6%, respectively. Recurrence occurred in 7 (14%) patients with a median survival time of 16.7 months (range from 3 to 50 months). Six patients had recurrence in the abdominal space. The percentage of Ki67 ( P = .01) and tumor size ( P = .03) were 2 important prognostic factors in multivariate analysis. In terms of survival outcomes, fertility-preserving surgery can be equivalent to radical surgery. Sixteen patients tried to conceive, and 6 patients with advanced-stage succeeded in 10 pregnancies. Of these, 6 patients successfully gave birth to 6 healthy babies. Conclusions: The diagnosis of YST of childbearing age is very rare. Because the failure of primary treatment is related to the residual disease after salvage surgery, the fertility and survival results of patients undergoing fertility-preserving surgery are promising.